EKSPERIMENTASI MODEL PEMBELAJARAN THINK TALK WRITE (TTW) DAN THINK PAIR SHARE (TPS) PADA POKOK BAHASAN DIMENSI TIGA DITINJAU DARI KESULITAN BELAJAR SISWA KELAS X SMA NEGERI DI KABUPATEN MAGETAN TAHUN PELAJARAN 2012/2013 - Susmono, Susmono; Kusmayadi, Tri Atmojo; Mardiyana, Mardiyana (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objectives of this research were to find out: (1) which learning model of the TTW, TPS or conventional learning results in a better learning achievement in Mathematics; (2) which students with learning difficulties (low, medium or high) have a better learning achievement in Mathematics; (3) in each students learning difficulties, which learning model of TTW, TPS or conventional learning results in a better learning achievement in Mathematics; and (4) in each learning model, which students learning difficulties (low, medium or high) results in a better learning achievement in Mathematics.This research used the quasi experimental research method with the factorial design of 3x3. Its population was all of the students in Grade X of State Senior High Schools in Magetan regency. The samples of the research were taken by using the stratified cluster random sampling technique. The samples of the researh consisted of 232 students; 82 students belonged to experiment class one, 78 students belonged to experiment class two and 72 students belonged to control class. The data of the research were gathered through multiple choice test of learning achievement and questionnaire of students learning difficulties. The data of the research were analyzed by using the unbalanced two-way analysis of variance at the significance level of 5%. The results of the research showed that: (1) the TTW and TPS learning models result in the same good achievement in mathematics, the TTW and conventional result in the same good achievement, but TPS result in better than the conventional learning model; (2) The students with low learning difficulties result in better than with the high learning difficulties, the students with the low learning difficulties result in the same good with the medium learning difficulties, the students with the medium learning difficulties result in the same good with the students with high learning difficulties; (3) ) in each students learning difficulties, the TTW and TPS result in the same good learning achievement in mathematics, TTW and conventional result in the same good learning achievement in mathematics, TPS learning model result in Â better learning achievement than conventional; (4) in each learning model, the student with low learning difficulties result in Â better learning achievement than with high learning difficulties, the students with low learning difficulties result in the same good learning achievement with the medium learning difficulties, that with medium learning difficulties result in the same good learning achievement with the high learning difficulties.Keywords: learning model, TTW, TPS, conventional, students learning diffulties.